High-throughput shoot phenotyping reveals temporal growth responses to nitrogen and inorganic and organic phosphorus sources in tomato. Issue 2 (8th March 2023) - Ngo, Hue T T; Cavagnaro, Timothy R; Jewell, Nathaniel; Brien, Christopher J; Berger, Bettina; Watts-Williams, Stephanie J
Abstract: The application of nitrogen (N) and phosphorus (P) fertilizers to soils is required to maintain crop yields, so the sufficient and timely delivery of nutrients to match crop demand is important in fertilizer management. We quantified temporal growth responses of tomato plants with different rates of N and P application using high-throughput shoot phenotyping. The tomato plants were grown in soil that had organic, inorganic or a combination of sources of P incorporated. Additional N was added to each pot at low and high rates, 13 days after planting. At the same rate of total P application, the inorganic P source resulted in greater shoot growth at the early time points. Later on, the plants supplied with organic or mixed P sources grew faster than those that received the inorganic P source, resulting in comparable shoot biomass in all treatments at the time of destructive harvest. The shoot phenotyping data demonstrated that readily available soil P was important for early tomato growth while available N was more important in later stages of vegetative growth. These results suggest that a fertilizer formulation of combined inorganic and organic P sources may be able to sustain rapid and great shoot growth in tomato plants, while also reducing additional N input. Abstract : High-throughput phenotyping was used to track real-time plant growth of tomato plants and their responses to nutrients supplied from different sources and rates of phosphorus (P). The results suggest that the combined use of P-rich chicken litter (organic matter) and inorganic P sources can be used to close the growth gap between the sole use of organic fertilizer and the use of conventional P fertilizer. Furthermore, organic P fertilizers could reduce the need for additional nitrogen fertilizer.